The magnetic properties of epitaxial Fe100-xGax thin films: the role of Gallium composition and film thickness - Roy, Syamashree (2021)
Magnetostrictive smart materials in the form of thin films hold a lot of promise because of their utilisation in a variety of microelectromechanical (MEMs) and nanoelectromechanical (NEMs) based devices, magnetic memory and logic technology. A promising candidate is Galfenol which is an alloy of Fe and Ga, and has been demonstrated to have a very high magnetostriction coefficient in bulk single crystal form. Recently, the first measurement of magnetostriction in epitaxial thin films was reported by Parkes et al. who found that epitaxial thin films of Fe81Ga19 show magnetostriction values as large as the bulk material, making the epitaxial layers a prospective candidate for applications. It is therefore important to understand the role of Ga composition and film thickness in determining the magnetic properties of epitaxial Galfenol.